Session Topic: Empirical Research on Capital Markets: Discussion - Glauber, Robert R.; Ritter, Lawrence S. (Journal of Finance, 1975)
Robert R. Glauber, Lawrence S. Ritter, Session Topic: Empirical Research on Capital Markets: Discussion, The Journal of Finance, Vol. 30, No. 2, Papers and Proceedings of the Thirty-Third Annual Meeting of the American Finance Association, San Francisco, California, December 28-30, 1974 (May, 1975), pp. 674-676